Feasibility of postoperative concurrent chemoradiotherapy in Japanese patients with oral squamous cell carcinoma showing high-risk factors for recurrence. Issue 1 (January 2015) - Yamada, Shin-ichi; Yanamoto, Souichi; Takahashi, Hidenori; Naruse, Tomofumi; Shigeta, Takashi; Minamikawa, Tsutomu; Matsui, Taiki; Kakei, Yasumasa; Ikeda, Hisazumi; Minamizato, Tokutaro; Shiraishi, Takeshi; Asahina, Izumi; et al.
Abstract Concurrent chemoradiotherapy with high-dose single-agent cisplatin has been recognized worldwide as the standard treatment for resectable advanced head and neck squamous cell carcinoma with a high risk of recurrence. However, because of severe acute adverse events compared with radiation therapy alone, this regimen is still not widely used in Japan. Hence, we evaluated the feasibility and safety of this regimen in Japanese patients with oral squamous cell carcinoma having high risk factors for recurrence. Microscopically incomplete resection, extracapsular extension, and two or more lymph node metastases were defined as the high-risk factors. The treatment regimen included three cycles of cisplatin at a dose of 100 mg/m2 and concomitant radiation therapy (66 Gy/33 Fr). Nineteen patients were enrolled. The completion rate with a cumulative cisplatin dose of more than 200 mg/m2 was 78.9%, and 63.1% with a cumulative cisplatin dose of more than 240 mg/m2. With an average follow-up period for survivors of 15.8 months (range 3–46 months), 24-months LRC, RFS, and OS were 93.8%, 62.2%, and 79.1%, respectively. This cisplatin and concurrent radiation regimen is feasible for Japanese patients with oral squamous cell carcinoma having high-risk factors for postoperative recurrence.